ASSESSMENT OF THE STATE OF EMOTIONAL HEALTH OF UKRAINIAN UNIVERSITY STUDENT YOUTH THAT IS INVOLVED INTO DIFFERENT LEVELS OF PHYSICAL ACTIVITY - Yaroshyk, Marta; Malanchyk, Нalyna; Solovei, Alla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the present days, we encounter and can observe a widespread distribution of physical, moral and psychological crisis among the citizens of Ukraine. The most inclined to undergo and experience distress group of the population is higher educational institutions’ youth. Based on the data we have collected and carefully analyzed, we have discovered that regular exposure of a person to physical activity helps maintain the levels of distress and influence of other negatively oriented emotional states to their minimums whereas the physical activity positively impacts emotional health, especially in regard to student youth. Accordingly, our research is dedicated and conducted to investigate and assess how emotional health of Ukrainian students correlates with different levels of physical activity they experience. In order to complete the study, we asked a few female students that indeed take physical training (PT) classes at their universities, precisely, 48, to take part in our investigation. The participants were at the particular stages of their Bachelor’s program progression (from Freshmen to Senior Year students) at the moment of the study being conducted. We attempt to measure and assess the indices that constitute emotional health which we defined as a) mood, b) well-being, c) overall activity, and d) anxiety. Additionally, we determine the levels of physical activity of each student. Based on the evidence we have collected, the students evaluated their moods in the range of 56 10,0 points (high evaluation marks), their well-beings in the range of 5110,7 points (high evaluation marks), and the levels of their overall activity in the range of 439,5 points (average evaluation marks). Altogether, the vast majority of the participants marked their levels of trait and state anxieties as 473,9 points and 483,7 points, accordingly, that we define as high. On the other hand, we have discovered that most participants have low physical activity index that constitute into the value of 31. On the contrary, the ones whose physical activity is higher have stated that their state anxiety is lower — 46,33,4 points, — compared to those who involve into average and low exposure to physical activity — 47,23,5 points and 47,64,3 points, respectively. The potential of future studies of emotional health are highly dependent upon researches into emotions that students experience, how well students recognize, distinguish, and live through their feelings, as well as into the abilities of students to adapt to alternate vital circumstances.